OCURRENCE OF Bucephalus sp. (TREMATODA: BUCEPHALIDAE) IN Anomalocardia brasiliana (GMELIN, 1791) (MOLLUSCA: VENERIIDAE) AT CANTO DA BARRA BEACH, FORTIM, CEARÁ STATE, BRAZIL - Araújo, Maria Lúcia Rodrigues; Rocha Bareira, Cristina de Almeida (Arquivos de Ciências do Mar, 2017)
This present paper reports the ocurrence of trematods preyng upon the venerid bivalve Anomalocardia brasiliana, na inhabitant of Sandy and muddy bottoms of Jaguaribe River estuary, Canto da Barra Beach, Fortim, Ceará State, Brazil. Among 469 individuals, 6% os them were shown to be preyed upon. Sporocysts and cercariae of Bucephalus so were located mainly on the gonads of A. brasiliana, where they caused disruption os the ovarian folicular walls and testicular ducts and destroued the germ cells. In some cases the parasite activities prevent sexual differentiation. The ocorrence of those parasites may be related to environmental parameters, such as temperature, salinity and food availability, as well as to human impacto n estuarine environment. Although the prevalence of Bucephalus sp. was low in the A.brasiliana population from canto da Barra Beach, its increase could seriosly affect the population structure of this clam in the region.